Time is an Illusion. - NEVILLE-NEIL, GEORGE V. (Communications of the ACM, 2016)
The article discusses timekeeping in distributed computing systems. Particular focus is given to problems surrounding synchronization and syntonization. Details on Network Time Protocol (NTP) and on the ways in which computers' quartz crystals are affected by environmental conditions are presented. Other topics include the use of Precision Time Protocol (PTP) in high-frequency trading (HFT) and the variations in packet transit time between master and slave systems, also known as jitter.